(untitled) (The International Journal for Scientific Research, 2026)
This study addresses the issue of the 10-month contracts prevalent among private schools in the Kingdom of Saudi Arabia, which are limited to the actual duration of the school year—approximately 10 months—and do not include the summer vacation period, in order to avoid financial obligations during the summer. The research question centers on how to reconcile the economic and investment aspects of private schools with their educational and pedagogical nature. This is because certain administrative decisions of an economic nature have an impact on teachers’ job security and, consequently, on their financial and psychological well-being; all of which, in turn, affects the educational institution as a whole. This study therefore examines the circumstances that gave rise to this practice – the ten-month contracts – and their legality in light of the provisions of the Saudi Labor Law and its implementing regulations, as well as their implications for teachers and educational institutions. It also examines how to balance the teacher’s right to job security with the right of private schools to achieve their legitimate objectives, all in a manner that does not conflict with the educational and pedagogical mission of the schools. This study is divided into two sections, each of which includes two subsections. The first section addresses the nature of employment contracts in private schools, with the aim of identifying the contract most suited to the nature of the educational process and the nature of a teacher’s work. The second section examines the ten-month contract, its motivations, and its implications, to understand its purpose, the circumstances that led to its creation, and its impact on teachers. Finally, the study reached several conclusions, the most notable of which is that 10-month contracts are not, in and of themselves, a violation of the law; rather, the problem lies in how they are used. The study also identified a set of recommendations aimed at stabilizing employment contracts in private schools, thereby ensuring the stability of the educational process as a whole.